1995
DOI: 10.1007/3-540-60045-0_48
|View full text |Cite
|
Sign up to set email alerts
|

It usually works: The temporal logic of stochastic systems

Abstract: In this paper the branching time logic pCTL* is defined.pCTL* expresses quantitative bounds on the probabilities of correct behavior; it can be interpreted over discrete Markov processes. A bisimulation relation is defined on finite Markov processes, and shown to be sound and complete with respect to pCTL*. We extend the universe of models to generalized Markov processes in order to support notions of refinement, abstraction, and parametrization. Model checking pCTL* over generalized Markov processes is shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
183
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(184 citation statements)
references
References 13 publications
1
183
0
Order By: Relevance
“…In the following, we sketch the proof of Theorem 7 (2). In the proof we use 'equivalent' for 'equivalent over the probabilistic structure generated by ðM, s 0 Þ)'.…”
Section: Theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…In the following, we sketch the proof of Theorem 7 (2). In the proof we use 'equivalent' for 'equivalent over the probabilistic structure generated by ðM, s 0 Þ)'.…”
Section: Theoremmentioning
confidence: 99%
“…The first applications of temporal logic to probabilistic systems were considered while studying which temporal properties are satisfied with probability 1 by systems modeled as finite Markov chains [17]. Later, references [12,2] introduced pCTL and pCTL* logics that can express quantitative bounds on the probability of system evolutions. This approach is surveyed, e.g., in [11,4,19].…”
Section: Introductionmentioning
confidence: 99%
“…A first work in this direction was [4]; it showed that bisimilarity and stuttering bisimilarity are, respectively, in full agreement with the logical equivalences induced by CTL* and by CTL* without the next-time operator when interpreted over Kripke structures (state-labeled transition systems) [5]. In a subsequent work, it was shown that the equivalence induced by the probabilistic temporal logic PCTL*, interpreted over probabilistic Kripke structures, coincides with probabilistic bisimilarity [1]. A more recent work is [25], which introduces new probabilistic bisimilarities that are in full agreement with the logical equivalences induced by PCTL, PCTL*, and their variants without the next-time operator interpreted over nondeterministic and probabilistic Kripke structures [3].…”
Section: Introductionmentioning
confidence: 90%
“…Finally, we denote by PML ∃,I and PML ∀,I two further variants generalizing the previous two logics, in which the probability value p is replaced by a prob- 1] are such that p 1 ≤ p 2 -and the resulting diamond operator is interpreted as follows:…”
Section: Bisimilarity For Non-alternating and Alternating Processesmentioning
confidence: 99%
See 1 more Smart Citation